The present and the future of degradable dendrimers and derivatives in theranostics - Leiro, Victoria (2019)
Interest in dendrimer-based nanomedicines has been growing recently, as it is possible to precisely manipulate the molecular weight, chemical composition, and surface functionality of dendrimers, tuning their properties according to the desired biomedical application. However, one important concern about dendrimer-based therapeutics remains-the nondegradability under physiological conditions of the most commonly used dendrimers. Therefore, biodegradable dendrimers represent an attractive class of nanomaterials, since they present advantages over conventional nondegradable dendrimers regarding the release of the loaded molecules and the prevention of bioaccumulation of synthetic materials and subsequent cytotoxicity. Here, we present an overview of the state-of-the-art of the design of biodegradable dendritic structures, with particular focus on the hurdles regarding the use of these as vectors of drugs and nucleic acids, as well as macromolecular contrast agents.